毛細管膜型人工肺（テルモ社，ホローファイバー，３．３Ｍ｀２´肺）の間欠的長時間使用で検討した性能の限界 - KAWAKAMI T.; IJU M.; WATANABE F.; MATSUURA M.; TAKAHASHI J.; TAKAHASHI A. (Jinko Zoki, 1981)
3.3M2 TERUMO Oxygenators were used in this study at 37°C. Six oxygenators were repeatedly reused in the functioning apparatus primed with diluted FC43·canine blood perfusate from 3 to 5 times, 165 to more than 200min, in each. No significant fall in its function on O2 tranfer and CO2 control of the perfusate was observed throughout up to 5 times' reuse, reaching to more than 900min in total perfusion time, with minimum increasing tendency of perfusate hemolysis. Hemodynamic study on relationship between flow through the oxygenator and inlet line pressure and hemolysis of the perfusate was carried out by use of a closed circuit primed with reasonablly diluted heparinized canine whole blood. Perfect corelation was demonstrated between them under the tested flow (500-1500ml/min), disclosing less than 200mmHg line pressure and 140mmHg pressure gradient through the oxygenator with less than 0.3mg/dl/min free plasma hemoglobin concertration when 65mmHg afterload was applied. Hemodynamically, acceptable flow limit of this oxygenator would be more than 2000ml/min judging from present datas.